2007
DOI: 10.1007/s10886-007-9261-x
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids in Bufonid Toads (Melanophryniscus): Temporal and Geographic Determinants for Two Argentinian Species

Abstract: Bufonid toads of the genus Melanophryniscus represent one of several lineages of anurans with the ability to sequester alkaloids from dietary arthropods for chemical defense. The alkaloid profile for Melanophryniscus stelzneri from a location in the province of Córdoba, Argentina, changed significantly over a 10-year period, probably indicating changes in availability of alkaloid-containing arthropods. A total of 29 alkaloids were identified in two collections of this population. Eight alkaloids were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 32 publications
5
49
0
1
Order By: Relevance
“…Alkaloid defenses in these mantellids are entirely dependent on a diet of alkaloid-containing arthropods, and it is hypothesized that differences in their chemical defenses are due largely to the availability of arthropods among geographic locations (Saporito et al 2009). Variation in alkaloid composition among geographic locations has been described in other species of Mantella (see Andriamaharavo et al 2010;Clark et al 2006;Daly et al 1996Daly et al , 2008Garraffo et al 1993a), and appears to be a general characteristic common to all poison frogs (see Daly et al 2007;Garraffo et al 1993b;Saporito et al 2006Saporito et al , 2007aSaporito et al , 2009 Interestingly, some dietary studies of mantellid frogs have reported that ants represent a major food source for certain species (Clark et al 2005;Vences and Kniel 1998;). Vences and Kniel (1998) studied the stomachs of seven M. haraldmeieri, three M. nigricans, four M. laevigata, and one M. ebenaui (as M. betsileo), and reported ants as prevalent prey in all of these species, with an overall numeric proportion of 74 %.…”
Section: Discussionmentioning
confidence: 93%
“…Alkaloid defenses in these mantellids are entirely dependent on a diet of alkaloid-containing arthropods, and it is hypothesized that differences in their chemical defenses are due largely to the availability of arthropods among geographic locations (Saporito et al 2009). Variation in alkaloid composition among geographic locations has been described in other species of Mantella (see Andriamaharavo et al 2010;Clark et al 2006;Daly et al 1996Daly et al , 2008Garraffo et al 1993a), and appears to be a general characteristic common to all poison frogs (see Daly et al 2007;Garraffo et al 1993b;Saporito et al 2006Saporito et al , 2007aSaporito et al , 2009 Interestingly, some dietary studies of mantellid frogs have reported that ants represent a major food source for certain species (Clark et al 2005;Vences and Kniel 1998;). Vences and Kniel (1998) studied the stomachs of seven M. haraldmeieri, three M. nigricans, four M. laevigata, and one M. ebenaui (as M. betsileo), and reported ants as prevalent prey in all of these species, with an overall numeric proportion of 74 %.…”
Section: Discussionmentioning
confidence: 93%
“…The numbers in parenthesis represent the number of unique alkaloids present. The column ''All poison frogs'' represents the combined number of alkaloids identified for each alkaloid class a Other than the pyridinic epibatidine alkaloids, and including the alkaloids nicotine, pyridylnicotine, and noranabasamine b Other than the indolic pseudophrynamine alkaloids, and including the alkaloids calycanthine and chimonanthine c Alkaloids with an ''izidine'' structure, that cannot be placed into one of the several izidine classes d Alkaloids that have not been classified to structural class e Includes: adenine, dihydroPTX, N-methylpyrrolidine, octahydroquinoline, and tetrahydroquinoline * Identified in mixed arthropod samples, including mites Data are updated from Daly et al 2005 and includes, Clark et al 2005;Mebs et al 2005;Clark et al 2006;Saporito et al 2007b, c;Daly et al 2007;Daly et al 2008a, b;Daly et al 2009;Andriamaharavo et al 2010;Saporito et al unpublished data Most alkaloids in poison frogs have branch-points in their carbon skeleton; the alkaloids containing no branchpoints presumably are derived from linear precursors. These differences appear to be related to specific arthropod sources (see ''Arthropod sources for alkaloids'').…”
Section: Alkaloid Diversity In Poison Frogsmentioning
confidence: 99%
“…However, there are also examples of differences in alkaloid composition among populations of different species at the same location (e.g., Daly et al 2008b;Myers et al 1995). Alkaloid composition changes temporally and seasonal changes in arthropod availability may explain part of this temporal variation (e.g., Daly et al 2007;Saporito et al 2006Saporito et al , 2007c. Juvenile poison frogs contain smaller quantities of alkaloids than do adults (e.g., Daly et al 2002).…”
Section: Variation In Alkaloids Among Poison Frogsmentioning
confidence: 99%
“…Several studies have examined geographic and temporal variation of the type, number, and amount of alkaloids present in poison frog and toad populations, showing that up to 26 different alkaloids can be evident within a single individual (Clark et al, 2006;Saporito et al, 2006Saporito et al, , 2007aDaly et al, 2007). Poisonous frogs typically had more similar alkaloid profiles within a locality than among localities, attributable to differences in the diversity of alkaloid-content in prey within the arthropod assemblages at different localities (Saporito et al, 2004(Saporito et al, , 2006(Saporito et al, , 2007aMebs et al, 2005;Clark et al, 2006;Daly et al, 2007Daly et al, , 2008. These studies also found temporal variation of alkaloid diversity within a population suggesting effects of seasonal changes, increase in habitat disturbances, and forest dynamics (Clark et al, 2006;Saporito et al, 2006).…”
mentioning
confidence: 99%